Tinjauan atas Penerapan Pajak pada Perdagangan Melalui Sistem Elektronik dalam Perspektif Peraturan Perpajakan Saat Ini - Dwi Resti Pratiwi (Pusat Kajian Anggaran, 2021)
This study examined the tax policy of the digital economy in Indonesia to help recover the economy during and after the Covid-19 pandemic. It used a qualitative approach to review the taxing policy on the digital economy in Indonesia. The results showed that unilateral action by the Government of Indonesia in imposing a direct tax on over-the-top (OTT) electronic transactions is hard and challenging. This is because it needs the global consensus for taxation of the digital economy. Otherwise, the tax policies are likely to contradict one another, causing double taxation for multinational companies. In addition, there are issues that arise from imposing VAT on the digital economy. First, ensure that the foreign tax collector complies with the Indonesia VAT regulation. Second, the determination of consumer criteria for digital products is easy to ignore. The prerequisite for using Indonesian IP can be avoided by a virtual private network to use the domain of another country. Therefore, this study suggests that the Government of Indonesia must encourage a global consensus on a digital tax framework that benefits all parties. Furthermore, the Directorate General of Tax (DGT) must enforce data exchange from financial institutions and take serious actions against non-compliance.